Clinical engineers in the 21st century. - Zambuto, R.P (IEEE Engineering in medicine and biology magazine)
The primary mission of clinical engineering for the past 40 years has been in areas of medical equipment and technology management. With the turn of the century, driven by the rise of information technology in healthcare, the focus of clinical engineering is shifting towards clinical systems integration, with a concentration in patient safety. This paper presents the historical roles of clinical engineers, recent changes in clinical engineering and future advances in clinical engineering.